2014
DOI: 10.1111/appy.12127
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm characteristics, poor sleep quality, daytime sleepiness and common psychiatric disorders among Thai college students

Abstract: Objective To investigate the relationship between common psychiatric disorders (CPDs) and sleep characteristics (evening chronotype, poor sleep quality and daytime sleepiness) among Thai college students. Methods A cross-sectional study was conducted among 2,970 undergraduate students in Thailand. Students were asked to complete a self-administered questionnaire that collected information about lifestyle and demographic characteristics. The Horne and Ostberg Morningess-Eveningeness Questionnaire (MEQ), Pitts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
3
21
1
3
Order By: Relevance
“…The General Health Questionnaire-12 (GHQ-12) was used to evaluate the presence of common psychiatric disorders (CPDs). Using logistic regression models, they found a significant association between CPDs and sleep characteristics, such as evening chronotype, poor sleep quality and daytime sleepiness (Haregu et al 2015). To our knowledge, so far no one has checked whether sleep quality variables depend on the season in which the questionnaire has …”
Section: Sleep Variables: Chronotype and Seasonmentioning
confidence: 99%
“…The General Health Questionnaire-12 (GHQ-12) was used to evaluate the presence of common psychiatric disorders (CPDs). Using logistic regression models, they found a significant association between CPDs and sleep characteristics, such as evening chronotype, poor sleep quality and daytime sleepiness (Haregu et al 2015). To our knowledge, so far no one has checked whether sleep quality variables depend on the season in which the questionnaire has …”
Section: Sleep Variables: Chronotype and Seasonmentioning
confidence: 99%
“…This finding is in agreement with findings reported by other investigators. For instance in a study of Thai college students, we found that in a multivariate adjusted model, the odds of CMDs was increased two-fold among students with daytime sleepiness as compared with those without the risk factor (OR=1.95; 95% CI 1.54-2.47) [7]. Similarly, Bixler and colleagues (2013) reported that excessive daytime sleepiness was strongly associated with depression than sleep-disordered breathing (e.g., due to sleep apnea) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral characteristics such as excessive consumption of caffeinated products, consumption of Khat, and smoking are also shown to have an adverse effect on daytime sleepiness and mental health [6]. An accumulating body of literature documents that sleep disturbances such as sleep quality, sleep duration, excessive daytime sleepiness are associated with common mental disorders (CMDs) [7-10]. However, few studies have focused on the relation between OSAS with CMDs.…”
Section: Introductionmentioning
confidence: 99%
“…Some E‐types have even expressed a feeling akin to jet lag (now referred to as “social jet lag”) in the early week as they attempt to retrain earlier weekday rising following later rising on weekends (e.g., Crowley & Carskadon, ; Wittmann, Dinich, Merrow, & Roenneberg, ). Compulsions such as extreme Internet usage; aggression; and addictions to substances, gambling, and sex have also been reported (e.g., Abasiubong et al, ; Digdon & Landry, ; Lin & Gau, ; Randler & Vollmer, ; Randler et al, ; Whittier et al, ) as has an association between eveningness and psychiatric disorders (e.g., Haregu et al, ; Tavernier & Willoughby, ).…”
mentioning
confidence: 99%
“…Not surprisingly, then, research on the effects of differing chronotypes on college student behavior has been conducted at numerous universities in the United States as well as many other countries, including Australia, Brazil, Canada, Chile, Ethiopia, Germany, India, Japan, Korea, Lebanon, Nigeria, Norway, Peru, Russia, Spain, Switzerland, Taiwan, Thailand, and Turkey. These studies have examined such diverse issues as general academic performance and achievement (e.g., Beşoluk, Önder, & Deveci, ; Borisenkov, Perminova, & Kosova, ; Medeiros, Mendes, Lima, & Araujo, ; Song & Stough, ), sleep habits and patterns (e.g., Azevedo et al, ; Cofer et al, ; Concepcion et al, ; Kabrita, Hajjar‐Muca, & Duffy, ; Medeiros et al, ; Park, Matsumoto, Seo, Shinkoda, & Park, ; Robinson et al, ; Tavernier & Willoughby, ; Urner et al, ; Yadav & Singh, ; Zimmermann, ), the influence of external synchronizers (e.g., Teixeira et al, ), physical performance (Vitale, Calogiuri, & Weydahl, ) and issues related to health, problem and at‐risk behaviors, and psychological disorders (e.g., Abasiubong, Abiola, & Udofia, ; Culnan, Kloss, & Grandner, ; Digdon & Howell, ; Digdon & Landry, ; Haregu et al, ; Lin & Gau, ; Randler, Horzum, & Vollmer, ; Randler & Vollmer, ; Tavernier & Willoughby, ; Whittier et al, ).…”
mentioning
confidence: 99%